Persistence and Safety of Golimumab in Elderly Patients with Rheumatoid Arthritis and Renal Dysfunction in a Real-World Setting - Seiji Yokoyama; Yutaka Ishii; Junya Masuda (Adis, Springer Healthcare, 2022)
Abstract Background The efficacy and safety of golimumab in elderly patients with renal dysfunction are not well evaluated due to the exclusion criteria of clinical trials. Objective To assess the persistence and safety of golimumab in elderly rheumatoid arthritis patients with renal dysfunction. Patients and Methods In this retrospective observational study, we used Japan's nationwide electronic medical records and claims database to identify patients aged 65 years and older who were newly prescribed golimumab for rheumatoid arthritis between July 2011 and June 2018. Patients were divided into three groups according to estimated glomerular filtration rate (eGFR; high, ≥ 90; moderate, ≥ 60, < 90; low, ≥ 30, < 60), and the persistence of golimumab and adverse events were compared between the groups. Results A total of 423 patients met the eligibility criteria. At 6 months, the persistence rates of golimumab were 62.4%, 63.7% and 67.0% in the high, moderate and low eGFR groups, respectively. In Cox proportional hazards regression analysis, baseline eGFR was not associated with golimumab persistence or adverse events, but concomitant methotrexate and low baseline C-reactive protein (CRP) were associated with longer golimumab persistence. Conclusion Reduced renal function was not associated with continuation of golimumab or incidence of adverse events, suggesting that the persistence of golimumab therapy in patients with rheumatoid arthritis is independent of the baseline level of renal function. On the other hand, concomitant use of methotrexate and low baseline CRP levels were suggested as factors that may affect the persistence of golimumab treatment.